HUBUNGAN ANTARA GAYA PENGASUHAN ORANG TUA TIPE ENABLING DAN CONSTRAINING DENGAN KOMITMEN DAN PEMBENTUKAN STATUS IDENTITAS KEBERAGAMAAN REMAJA AKHIR - Endin Nasrudin (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2008)
A significant correlation was found, between the enabling parental style to exploration in the domain of religion identity status; between the anabling parental style to commitment, and between the constraining parental style to exploration. No relationship was found between the constraining parental style and commitment in the domain of religious identity status. Suggestion for further research would be to identity other variables connected with identity status in the religion domain.